Formation of equiaxed α during ageing in a severely deformed metastable β Ti alloy. (November 2016) - Zafari, A.; Xia, K.
Abstract: Careful TEM examination has confirmed the formation of equiaxed α in nanocrystalline β during ageing of a severely deformed metastable β Ti alloy. It is revealed that the Burgers orientation relationship is obeyed upon α nucleation, but grain growth has led to the eventual incoherent α/β interfaces. In addition, intragranular acicular α would form when the β grains prior to ageing are much coarser than 10 nm. Graphical abstract: